Warm-up strategies of elite triathletes competing in the International Triathlon Union World Triathlon Series and Paratriathlon events: A case study - Stevens, C. J.; Peterson, B.; Pluss, M.; Novak, A. (The Journal of Sport and Exercise Science, 2020)
The use of a warm-up is a widely recommended and adopted strategy for athletes to optimise performance. However, limited recommendations about the optimal warm-up strategy for triathletes exist. Therefore, the purpose of this study was to investigate the warm-up strategies of elite triathletes in preparation for competition. Ten elite triathletes (n=6 female and n=4 male, age: 26.8±6.1 y) currently competing in the International Triathlon Union World Triathlon Series (n=8) or Paratriathlon Series (n=2) and including both Olympic and Paralympic medalists, completed a survey about their warmup routine. For the World Series athletes, the range in total warm-up duration was 25-55 min, which included 8-20 min of swimming, 0-30 min of cycling, and 5-25 min of running. For the Paratriathlon athletes, the range of total warm-up duration was 15-25 min, which included 5-15 min of swimming, 0-10 min of cycling, and 0-10 min of running. Elite triathletes finished their warm-up 13±5 min prior to race start. The inclusion of additional warm-up strategies varied in frequency: dynamic activation drills (7/10; 70%), short sprints (7/10; 70%), static stretching (5/10; 50%), technique drills (5/10; 50%), static muscle activations (3/10; 30%), foam rolling (2/10; 20%) and massage (0/10; 0%). There is a large range in the duration and intensities of the warm-up strategies amongst elite triathletes, which highlights the individual needs of the athletes and/or a lack of scientific recommendations available. Future research should be based on current practice to begin to develop an optimal warm-up routine for triathletes. Developing athletes can experiment with modified versions of current practice during training in scenarios simulating competition.